The Types of Process Used In BTS’ Song Lyrics - Diani Syahputri; Nadya Auliana Putri (English Teaching and Linguistics Journal (ETLiJ), 2022)
This study deals with types of process in BTS’ song lyrics. The objectives of the study were to find out the types of process, to determine the dominant types of process  and to describe the implication of the types of process used in BTS’ song lyrics. Ten songs were taken as the data and analysed by descriptive qualitative method. The data were collected using the documentation method. The data was analysed through Miles & Huberman (2014:266) that involved: (1) data condensation, (2) data display, and (3) conclusion drawing. The finding of research showed that all types of process used in BTS’ song lyrics and there were 286 clauses in the BTS’ song lyrics. The most dominant types of process used in BTS’ song lyrics was material process with 92 (32.17%) occurrence Then it is followed by relational process with 91 (31.82%) occurrence, mental process with 65 (22.73%) occurrences, verbal process with 18 (6.29%) occurrences, behavioural process with 13 (4.54%) occurrences, and the last existential process with 7 (2.45%) occurrences. The implication of types of process used in BTS’ song lyric was to find that the BTS’ song lyrics can aid development and  support the assertion that music and rhyme as well as to increase the ability in spatial reasoning which leads to the greater success in the future, and this song lyric indicates the activities or events that happen in the outside of human beings, it means that this song lyrics contain about activity, action or events so that  all were happened or done as physically and materially. The action or physical verbs are mostly used